Noninvasive Facial Rejuvenation. Part 1: Patient-Directed - Commander, Sarah Jane; Chang, Daniel; Fakhro, Abdulla; Nigro, Marjory G.; Lee, Edward I. (Seminars in Plastic Surgery, 2016)
A proper knowledge of noninvasive facial rejuvenation is integral to the practice of a cosmetic surgeon. Noninvasive facial rejuvenation can be divided into patient- versus physician-directed modalities. Patient-directed facial rejuvenation combines the use of facial products such as sunscreen, moisturizers, retinoids, α-hydroxy acids, and various antioxidants to both maintain youthful skin and rejuvenate damaged skin. Physicians may recommend and often prescribe certain products, but the patients are in control of this type of facial rejuvenation. On the other hand, physician-directed facial rejuvenation entails modalities that require direct physician involvement, such as neuromodulators, filler injections, laser resurfacing, microdermabrasion, and chemical peels. With the successful integration of each of these modalities, a complete facial regimen can be established and patient satisfaction can be maximized. This article is the first in a three-part series describing noninvasive facial rejuvenation. The authors focus on patient-directed facial rejuvenation. It is important, however, to emphasize that even in a patient-directed modality, a physician's involvement through education and guidance is integral to its success.
Keywords: photoaging; noninvasive facial rejuvenation; skin care; patient-directed facial rejuvenation